2015
DOI: 10.1242/dev.119339
|View full text |Cite
|
Sign up to set email alerts
|

Scalloped and Yorkie are required for cell cycle re-entry of quiescent cells after tissue damage

Abstract: Regeneration of damaged tissues typically requires a population of active stem cells. How damaged tissue is regenerated in quiescent tissues lacking a stem cell population is less well understood. We used a genetic screen in the developing Drosophila melanogaster eye to investigate the mechanisms that trigger quiescent cells to re-enter the cell cycle and proliferate in response to tissue damage. We discovered that Hippo signaling regulates compensatory proliferation after extensive cell death in the developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Proper Warts/LATS kinase function requires the N-terminal extension, which mediates interactions with both positive and negative regulators (Yabuta et al, 2013;Furth and Aylon, 2017). Recruitment of Warts/LATS kinases to the cell membrane requires the N-terminal extension in flies and humans, primarily through association with one of several proteins: Expanded, Merlin/NF2, and Ajuba (Hamaratoglu et al, 2005;Das Thakur et al, 2010;Yin et al, 2013;Rauskolb et al, 2014;Meserve and Duronio, 2015;Yu et al, 2015;Su et al, 2017;Ibar et al, 2018). The potential for competition between Mob1 and other regulators with overlapping binding domains has been uncovered for Warts/LATS kinase association with the LIM proteins, fly Ajuba, and human TRIP6.…”
Section: Competition Between Mob1 and Lim Proteins For Binding To Warmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper Warts/LATS kinase function requires the N-terminal extension, which mediates interactions with both positive and negative regulators (Yabuta et al, 2013;Furth and Aylon, 2017). Recruitment of Warts/LATS kinases to the cell membrane requires the N-terminal extension in flies and humans, primarily through association with one of several proteins: Expanded, Merlin/NF2, and Ajuba (Hamaratoglu et al, 2005;Das Thakur et al, 2010;Yin et al, 2013;Rauskolb et al, 2014;Meserve and Duronio, 2015;Yu et al, 2015;Su et al, 2017;Ibar et al, 2018). The potential for competition between Mob1 and other regulators with overlapping binding domains has been uncovered for Warts/LATS kinase association with the LIM proteins, fly Ajuba, and human TRIP6.…”
Section: Competition Between Mob1 and Lim Proteins For Binding To Warmentioning
confidence: 99%
“…Ajuba inhibition of Warts/LATS kinase activity was studied in epithelial cells of fly wing primordia. Inactive Warts/LATS is enriched at adherens junctions, where it binds to its inhibitor, Ajuba (Das Thakur et al, 2010;Rauskolb et al, 2014;Meserve and Duronio, 2015). Active Warts/LATS resides more apically, where it binds to Expanded and Merlin/NF2 complexes (Hamaratoglu et al, 2005;Yin et al, 2013;Sun et al, 2015;Yu et al, 2015;Su et al, 2017).…”
Section: Competition Between Mob1 and Lim Proteins For Binding To Warmentioning
confidence: 99%
“…Expression of Unpaired, the ligand upstream of the JAK/STAT pathway is activated by both JNK [40, 49, 51] and the p38 kinase [40]. Following tissue damage, the Hippo pathway is inhibited by the LIM-domain protein Ajuba, likely in response to changes in cell tension, resulting in increased Yki activity [54, 55]. Cross-talk between these pathways is likely; for example, Yki can activate Myc expression [59].…”
Section: Regenerative Growthmentioning
confidence: 99%
“…Studies in Drosophila have identified a mechanism for biomechanical regulation of Hippo signaling involving tensiondependent recruitment of Warts into a complex at the adherens junctions with the Drosophila Ajuba family protein Jub (Rauskolb et al, 2014). Jub, which contributes to regulation of Hippo signaling during development and regeneration (Das Thakur et al, 2010;Meserve and Duronio, 2015;Sun and Irvine, 2011), is recruited to adherens junctions in a tension-dependent manner (Rauskolb et al, 2014). Jub is an inhibitor of Warts (Das Thakur et al, 2010), and recruitment of Warts to Jub complexes also prevents it from localizing to other junctional and apical complexes where Warts activation occurs (Su et al, 2017;Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%